2009
DOI: 10.1002/ijc.24208
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine suppresses tumor growth and angiogenesis of gliomas in rats

Abstract: Tetrandrine, a bisbenzylisoquinoline alkaloid, has antitumor effects against some cancers, but its effects on gliomas are unknown. In this study, we investigated the effects of tetrandrine on the growth and angiogenesis of rat RT-2 gliomas. We treated RT-2 glioma cells with tetrandrine and then measured cytotoxicity, apoptosis and expression of vascular endothelial growth factor (VEGF). We also examined the cytotoxic effect of tetrandrine on the ECV304 human umbilical vein endothelial cells and the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…23) In the present study, we investigated the mechanism behind the antiproliferative effects of fangchinoline in breast cancer cells. Our study demonstrated that cancer cells treated with fangchinoline led to marked chromatin condensation and nuclear fragmentation, a biochemical hallmark of apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…23) In the present study, we investigated the mechanism behind the antiproliferative effects of fangchinoline in breast cancer cells. Our study demonstrated that cancer cells treated with fangchinoline led to marked chromatin condensation and nuclear fragmentation, a biochemical hallmark of apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Tetrandrine have been demonstrated to inhibit lipid peroxidation and platelet aggregation and reduces ischemia/reperfusion injury (28)(29)(30) and tetrandrine suppressed T and B cells and inhibited the production of cytokines (29). It was reported that tetrandrine is cytotoxic to RT-2 glioma cells and it has antitumor effects on subcutaneous and intracerebral gliomas, and inhibits angiogenesis in subcutaneous gliomas (31)(32)(33)(34). Tetradine induced apoptosis by activating reactive oxygen species and repressing Akt activity in human hepatocellular carcinoma HCC cells (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that TET exhibits anti-inflammatory and anticancer activity (Xu et al, 2006;Liu et al, 2008;Chen et al, 2009;Wu et al, 2010). It has been reported that TET may target regulatory signaling pathways that are involved in cell cycling and cytotoxicity (Lee et al, 2002;Meng et al, 2004;Ng et al, 2006).…”
mentioning
confidence: 99%